Individual differences and specificity of prefrontal gamma frequency-tACS on fluid intelligence capabilities - Santarnecchi, E; Muller, T; Rossi, S; Sarkar, A; Polizzotto, NR; Rossi, A; Cohen Kadosh, R (Elsevier, 2015)
Emerging evidence suggests that transcranial alternating current stimulation (tACS) is an effective, frequency-specific modulator of endogenous brain oscillations, with the potential to alter cognitive performance. Here, we show that reduction in response latencies to solve complex logic problem indexing fluid intelligence is obtained through 40 Hz-tACS (gamma band) applied to the prefrontal cortex. This improvement in human performance depends on individual ability, with slower performers at baseline receiving greater benefits. The effect could have not being explained by regression to the mean, and showed task and frequency specificity: it was not observed for trials not involving logical reasoning, as well as with the application of low frequency 5 Hz-tACS (theta band) or non-periodic high frequency random noise stimulation (101–640 Hz). Moreover, performance in a spatial working memory task was not affected by brain stimulation, excluding possible effects on fluid intelligence enhancement through an increase in memory performance. We suggest that such high-level cognitive functions are dissociable by frequency-specific neuromodulatory effects, possibly related to entrainment of specific brain rhythms. We conclude that individual differences in cognitive abilities, due to acquired or developmental origins, could be reduced during frequency-specific tACS, a finding that should be taken into account for future individual cognitive rehabilitation studies.